The Implementation of the Angel's Responsibility Toward the Duties of Teachers in the Modern Era - Zamzami, Alza Nabiel; Nafisa, Elly Zakiatin; Masrur, Masrur; Abdullah, Shodiq (UIN Mataram, 2024)
This research aims to examine how the values of faith in angels, especially in terms of responsibility, can be applied in more holistic educational practices in the modern era. This research uses a qualitative method with a literature approach. The analysis technique goes through three stages: Data condensation, data presentation, and conclusion drawing. The results of this study show that the implementation of angels' responsibility in carrying out their duties as teachers is very relevant and has a positive impact on the quality of education, both in terms of students' academic results and their character building. Trustworthiness in carrying out tasks, unconditional obedience, sincerity in every task, justice in carrying out tasks, and patience in carrying out heavy tasks are important elements that help teachers face various challenges that arise in the modern era. Teachers who emulate the nature of angels, who have integrity, sincerity, and a sense of responsibility, will be able to create a conducive learning environment and guide students to develop not only in knowledge but also in the formation of a strong character. Abstrak: Penelitian ini bertujuan untuk mengkaji bagaimana nilai-nilai keimanan kepada malaikat, khususnya dalam hal tanggung jawab dapat diterapkan dalam praktik pendidikan yang lebih holistik di era modern. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan. Teknik analisis melalui tiga tahapan: Kondensasi data, penyajian data, penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa Implementasi sifat tanggung jawab malaikat dalam menjalankan tugas sebagai guru sangat relevan dan memberikan dampak positif terhadap kualitas pendidikan, baik dalam hal hasil akademik siswa maupun pembentukan karakter mereka. Amanah dalam menjalankan tugas, kepatuhan tanpa syarat, keikhlasan dalam setiap tugas, keadilan dalam menjalankan tugas, dan kesabaran dalam menjalankan tugas berat merupakan elemen-elemen penting yang membantu guru dalam menghadapi berbagai tantangan yang muncul di era modern. Guru yang meneladani sifat malaikat, yang memiliki integritas, kesungguhan, dan rasa tanggung jawab, akan mampu menciptakan lingkungan pembelajaran yang kondusif, serta membimbing siswa untuk berkembang tidak hanya dalam ilmu pengetahuan, tetapi juga dalam pembentukan karakter yang kuat.